Poacic acid suppresses dollar spot and snow mould in amenity turfgrass. (11th November 2019) - Kabbage, M.; Piotrowski, J. S.; Thill, E.; Westrick, N. M.; Ralph, J.; Hockemeyer, K.; Koch, P. L.
Abstract : Plant‐based antifungal agents offer an alternative to synthetic fungicides in amenity turfgrass disease management. Poacic acid is a by‐product of the biofuel production process that has exhibited antifungal activity, and the objective of this research was to determine its ability to serve as an effective management tool for economically important turfgrass diseases such as dollar spot and snow moulds. In vitro and field tests were conducted in Wisconsin and Michigan, USA from 2015 to 2017 to determine the efficacy of poacic acid in suppressing the economically important turfgrass pathogens Clarireedia jacksonii and Microdochium nivale . Poacic acid demonstrated strong antifungal activity against both pathogens in vitro, inhibiting growth of C. jacksonii and M. nivale by 93% and 74% relative to nonamended media, respectively. Poacic acid reduced dollar spot in the field in one of two years, but failed to suppress snow mould when applied alone. Poacic acid was an effective mix partner for snow mould control when combined with a synthetic fungicide, an important attribute because no single fungicide currently on the market provides acceptable snow mould control under heavy disease pressure. Future research should focus on improving poacic acid field efficacy so that it can be incorporated into plant‐based disease management strategies for amenity turfgrass.